Diagnostic value of antibody responses to Mycobacterium avium subsp. paratuberculosis-derived proteins PtpA and PtpB in rheumatoid arthritis - Jorge Hernández-Bello; Sergio Cerpa-Cruz; Gabriela A. Sánchez-Zuno; Ferdinando Nicoletti; Horacio Bach; José F. Muñoz-Valle (PLoS ONE, 2026)
Evidence suggests that Mycobacterium avium subspecies paratuberculosis (MAP) may contribute to autoimmune diseases such as rheumatoid arthritis (RA), partly through effector proteins—particularly the tyrosine phosphatases PtpA and PtpB—that modulate macrophage signaling and promote bacterial persistence. This study evaluated whether serum antibodies against these proteins serve as biomarkers of RA. Humoral responses to PtpA and PtpB were quantified in Mexican RA patients (n = 100) and healthy controls (n = 100) using in-house ELISAs. Associations with disease activity (DAS28), ROC performance, and logistic regression models were assessed. Results showed that anti-PtpB antibody levels were significantly higher in patients with RA than in healthy controls (median OD 0.185 vs. 0.080; p < 0.0001) and had moderate discriminative capacity (AUC = 0.762). Anti-PtpB reactivity increased with higher disease activity and showed a significant positive association with DAS28 (p < 0.05). In addition, there was a functional disability measured by HAQ (p < 0.001), as well as moderate correlations with erythrocyte sedimentation rate and rheumatoid factor. A combined logistic regression model integrating both antibodies markedly improved diagnostic accuracy (AUC = 0.934), achieving high sensitivity (90%) and specificity (89%). These findings suggest a potential association of MAP with RA immunopathogenesis and indicate that combined quantification of anti-PtpA and anti-PtpB antibodies captures complementary and non-redundant immunological information. This combined serological approach may enhance RA diagnosis and provide clinically relevant insights into disease activity and severity.